Strata-bound anorthites in the Dachang Sn-polymetallic ore field, Guangxi, China - Pan, Jiahua; Amstutz, Christian; Moh, Günter (Chinese journal of geochemistry, 1993)
From the petrological study of ore-hosting rocks which contain large anorthite crystals and the occurrence and chemical composition of anorthites and related minerals, the authors consider that the large anorthite crystals are of authigenic origin.